US Supreme Court doctrine in the state high courts - Fix, Michael P. 1980-; Kassow, Benjamin J. ca. 20./21. Jh (Cambridge University Press, 2020)
US Supreme Court Doctrine in the State High Courts challenges theoretical and empirical accounts about how state high courts use US Supreme Court doctrine and precedent. Michael Fix and Benjamin Kassow argue that theories that do not account for the full range of ways in which state high courts can act are, by definition, incomplete. Examining three important precedents - Atkins v. Virginia, Lemon v. Kurtzman, and DC v. Heller/McDonald v. Chicago - Fix and Kassow find that state high courts commonly ignore Supreme Court precedent for reasons of political ideology, path dependence, and fact patterns in cases that may be of varying similarity to those found in relevant US Supreme Court doctrine. This work, which provides an important addition to the scholarly literature on the impact of Supreme Court decisions, should be read by anyone interested in law and politics or traditional approaches to the study of legal decision-making